Behavioral impairments in animal models for zinc deficiency - Hagmeyer, Simone; Haderspeck, Jasmin Carmen; Grabrucker, Andreas Martin (Frontiers in Behavioral Neuroscience, 2015)
Apart from teratogenic and pathological effects of zinc deficiency such as the occurrence of skin lesions, anorexia, growth retardation, depressed wound healing, altered immune function, impaired night vision, and alterations in taste and smell acuity, characteristic behavioral changes in animal models and human patients suffering from zinc deficiency have been observed. Given that it is estimated that about 17% of the worldwide population are at risk for zinc deficiency and that zinc deficiency is associated with a variety of brain disorders and disease states in humans, it is of major interest to investigate, how these behavioral changes will affect the individual and a putative course of a disease. Thus, here, we provide a state of the art overview about the behavioral phenotypes observed in various models of zinc deficiency, among them environmentally produced zinc deficient animals as well as animal models based on a genetic alteration of a particular zinc homeostasis gene. Finally, we compare the behavioral phenotypes to the human condition of mild to severe zinc deficiency and provide a model, how zinc deficiency that is associated with many neurodegenerative and neuropsychological disorders might modify the disease pathologies.